"Smart" IPN microgels with different network structures: Self-crosslinked vs conventionally crosslinked. (2nd August 2019) - Kozhunova, Elena Yu.; Vyshivannaya, Oxana V.; Nasimova, Irina R.
Abstract: Comparative study of thermo- and pH-sensitive conformational behavior of interpenetrating network (IPN) microgels based on poly(N-isopropylacrylamide) (PNIPA) and poly(acrylic acid) (PAA) with different network structures was conducted. For that purpose, PNIPA microgels were obtained by thermo-induced precipitation polymerization in the presence of the conventional cross-linking agent (N, N′-methylenebis(acrylamide)) and as a result of the self-crosslinking process. Then in situ polymerization of the acrylic acid network within these two types of PNIPA microgel particles was performed resulting in an IPN microgels formation. Dynamic and static light scattering methods were used for in-depth analysis of the system behavior in different conformational states of both networks of the IPN. The studies showed that the self-crosslinking method promoted the increase of pH-response of the system and its swelling ratio. The volume swelling ratio was about 3 times greater for the IPN microgels based on the self-crosslinked PNIPA microgels. Larger swelling coefficient is desirable, as it allows to expand the storage volume of a microgel particle. Graphical abstract: Image 1 Highlights: Thermo- and pH-sensitive IPN microgels were synthesized on the base of BIS-crosslinked and self-crosslinked PNIPA and PAA. DLS studies showed that self-crosslinking method promotes the increase of pH-response of the system and its swelling ratio. IPN MGs in a solvent which is poor for PNIPA network and good for PAA network have asymmetry factor of core-corona structure.